2018
DOI: 10.1021/acscentsci.8b00610
|View full text |Cite
|
Sign up to set email alerts
|

Why Are Saccharides Dehydrated in the Presence of Electrolytes? Insights from Molecular Modeling and Thermodynamic Measurements

Abstract: The mechanisms governing the interactions of neutral polar solutes with ions in aqueous solutions are still poorly understood, despite the importance of this phenomenon in many fields (chemistry, physicochemistry, biology, food industries). In order to go further through the understanding of the molecular mechanisms governing the ions’ specific effects, this paper presents a generic method dealing with the characterization and understanding of interactions between saccharides and ions in aqueous systems. For t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 29 publications
1
9
0
Order By: Relevance
“…For example, the variation in the apparent molar volumes of sucrose in the presence of NaCl and KCl has been attributed to the dehydration of the saccharide in presence of electrolyte (Sangster, Teng, & Lenzi, 1976). These results were later confirmed by other studies (Zhuo et al, 2000;Banipal et al, 2002). Recently, in the field of membrane separation, volumetric properties, which characterizes the saccharide hydration, have been used to understand the increase of the mass transfer of xylose, glucose, and saccharose through nanofiltration membranes in the presence of electrolytes (Boy, Roux de Balmann, & Galier, 2012).…”
Section: Introductionsupporting
confidence: 62%
See 1 more Smart Citation
“…For example, the variation in the apparent molar volumes of sucrose in the presence of NaCl and KCl has been attributed to the dehydration of the saccharide in presence of electrolyte (Sangster, Teng, & Lenzi, 1976). These results were later confirmed by other studies (Zhuo et al, 2000;Banipal et al, 2002). Recently, in the field of membrane separation, volumetric properties, which characterizes the saccharide hydration, have been used to understand the increase of the mass transfer of xylose, glucose, and saccharose through nanofiltration membranes in the presence of electrolytes (Boy, Roux de Balmann, & Galier, 2012).…”
Section: Introductionsupporting
confidence: 62%
“…quantities, such as the partial molar volume heat capacity (Banipal, Banipal, Ahluwalia, & Lark, 2002) or the apparent molar volume Shekaari and Kazempour, 2012), provide in formation on solute/electrolyte interactions and the solutes hydration properties. For example, the variation in the apparent molar volumes of sucrose in the presence of NaCl and KCl has been attributed to the dehydration of the saccharide in presence of electrolyte (Sangster, Teng, & Lenzi, 1976).…”
Section: Introductionmentioning
confidence: 99%
“…In our previous work, the hydration properties of ions in pure water have been studied via a stepwise solvation by adding one water molecule at a time and geometry optimizations were carried out without any symmetry constraints [33]. The water-shell around the solutes was obtained using the methodology proposed by Castro et al [34] for mercury compounds and also by Zhao et al [35] for samarium complexes.…”
Section: Ions Hydration Properties In Watermentioning
confidence: 99%
“…In our previous work [33], an analysis of the main structural and energy characteristics of Li + , Na + , K + , Mg 2+ , Ca 2+ and of Cl − , SO 4 2− , in pure water was carried out.…”
Section: Ions Properties In Pure Watermentioning
confidence: 99%
“…Additionally, it was also observed that the saccharide dehydration increases according to the following sequences: Na + < K + < Mg 2+ < Ca 2+ and Cl − < SO 4 2− , and that the anions (Cl − or SO 4 2− ) have no influence on the cation sequence [ 23 ]. Moreover, the saccharide hydration numbers, which reflect the solute hydration state, were also determined for the various electrolytes and the different concentrations investigated from the corresponding partial molar volume of saccharides [ 24 ].…”
Section: Introductionmentioning
confidence: 99%